2019
DOI: 10.1186/s40703-019-0097-3
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of rockfall hazards along NH-15: a case study of Al-Hada road

Abstract: Rock slope instability is major geohazards problems for both global and local. Geohazards phenomenon is the downward movement of rock blocks, debris or/and soil in response to gravitational stresses. The failures have classified according to the type of downslope movement either slides, rotational or flow [1]. One of the major causes of rock slope failure is the construction of the transportation system without a proper understanding of geological and geotechnical consideration of natural rock slopes [2-5]. Fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…respectively, where V s and I s are the phasor forms of V and I, respectively; j and ω are the imaginary number and angular frequency, respectively. The coupled V s and I s in Equations ( 7) and (8), respectively, are separated by taking the second derivative of V s in Equation (7) and employing Equation (8) as follows:…”
Section: Electromagnetic Waves In Transmission Linementioning
confidence: 99%
See 1 more Smart Citation
“…respectively, where V s and I s are the phasor forms of V and I, respectively; j and ω are the imaginary number and angular frequency, respectively. The coupled V s and I s in Equations ( 7) and (8), respectively, are separated by taking the second derivative of V s in Equation (7) and employing Equation (8) as follows:…”
Section: Electromagnetic Waves In Transmission Linementioning
confidence: 99%
“…For example, grout materials occasionally flow out due to gravity, resulting in a non-grouted part at the end of the rock bolt. Furthermore, the collapse of the wall, ground water flow, insufficient insertion depth of tremie pipe, improper withdrawal rate of tremie pipe, and poor consistency of the grout mixture, grout flowing into voids of a fractured rock mass may adversely affect the grout quality and create voids in the grout [3][4][5][6][7]. Lee et al [8] reported that the defect occurrence rate in tunnel construction is 15.8%.…”
Section: Introductionmentioning
confidence: 99%
“…A rock block could be a boulder or small group of independently moving rocks that separated with their rock mass body by the presence of discontinuities (Sazid 2019). The size of a rock block significantly influences how much of the impact a rock can cause when it falls over an object underneath.…”
Section: Rock Block Sizementioning
confidence: 99%
“…A rock block could be a boulder or small group of independently moving rocks that separated with their rock mass body by the presence of discontinuities (Sazid, 2019). The size of a rock block signi cantly in uences how much of the impact a rock can cause when it falls over an object underneath.…”
Section: Rock Block Sizementioning
confidence: 99%